Project Evaluation Method Based on Matter-Element and Hierarchy Model - Haifeng LI (Institute of Advanced Engineering and Science, 2012)
Project evaluation is always the key link of the engineering project management. Project evaluation is a complex work which involves many factors. The final evaluation result is always influenced directly by the definition of various evaluation indexes and the corresponding weight. Mainly study the judgment of the experts’ ability and the establishment of the project evaluation index system in the peer communication review, analyze deeply the engineering project review work, build a evaluation index system for the engineering project, and put forward a comprehensive evaluation method based on the matter-element and hierarchy model in the engineering project, at last, apply it in the actual project which proves the practicability of the paper’s theory. DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.622